Uji Aktivitas Antidiare Esktrak Etanol Daun Salam (Syzygium Polyanthum) Pada Men-cit (Mus muculus) - Shinta Mayasari (Journal Prima Health Science, 2020)
The examination effect of salam leaf ethanolic extract where the pur-posed of this study was to determine the effect and concentration of salam leaves as antidiarrheals. Ethanol extract dosages of salam leaf given orally (mg/kgbw) was 15; 20,25,30, and 35, carried out abserva-tions on mice starting diarrhea, weight of faeces, frequency diarrhea, and the duration of diarrhea for 5 hours. Loperamide HCl given dose of 1 mg/kg is used comparison with negative control CMC-Na, and comparison of Loperamide HCl was the 56th minute, 57,3; 57,9; 59; 58; 64,3 ; 54,3. Stool weight obtained an average of 0,34; 0,35; 0,32; 0,25; 0,27; 0,53; 0,21. The frequency of diarrhea was 8,8; 8,6; 8,9; 9,3; 8,6; 11,2; 8,5. Onset of diarrheal was average of minutes was 206,8; 207,6 ; 209,2; 209; 206,2; 230 and 88. From the research re-sults obtained ethanol extract salam leaves given antidiarrheal effects with an optimum dose of 35mg/kgbw